2011
DOI: 10.1016/j.aim.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The Lex-Plus-Powers Conjecture holds for pure powers

Abstract: We prove Evans' Lex-Plus-Powers Conjecture for ideals containing a monomial regular sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…, x a n n ). In this special case, Conjecture 1.2 (2) was proved in a series of papers [16,19,20], and Conjecture 1.2(1) was proved in [22] when the characteristic of K is 0. On the other hand, little is known for other Macaulay-Lex rings.…”
Section: Conjecture 12 (Mermin-peeva) Suppose That R = A/m Is Macaulmentioning
confidence: 93%
“…, x a n n ). In this special case, Conjecture 1.2 (2) was proved in a series of papers [16,19,20], and Conjecture 1.2(1) was proved in [22] when the characteristic of K is 0. On the other hand, little is known for other Macaulay-Lex rings.…”
Section: Conjecture 12 (Mermin-peeva) Suppose That R = A/m Is Macaulmentioning
confidence: 93%
“…Mermin and Murai, for instance, have shown that LPP2 holds in the case that I contains an regular sequence of monomials [7]. A survey on both EGH and LPP can be found in [6].…”
Section: Conjecture 5 (Lpp) Suppose That I ⊂ R Contains Anmentioning
confidence: 97%
“…The conjecture has been proven in the cases where L is an almost complete intersection [10], and when n D 2 [22]. Mermin-Murai [20] and Mermin-Peeva-Stillman [21] have interesting results related to the conjecture for ideals containing a monomial regular sequence. Recently, Caviglia-Maclagan [3] have proven that the EGH Conjecture is true if d j > P j 1 iD1 .d i 1/ for j D 1; : : : ; n. Thus, when n D 3 the outstanding cases for the EGH Conjecture are the "tight degrees" D D ¹d 1 ; d 2 ; d 3 º where…”
Section: Conjecture 25 (Eisenbud-green-harris (Egh) Conjecturementioning
confidence: 99%